Incidencia de queratoconjuntivitis seca en los conductores pertenecientes a cooperativas de taxis de la ciudad de Loja - Rodríguez Castillo, Dayanara Melissa (2022)
The present investigative work aimed to determine the incidence of keratoconjunctivitis in drivers belonging to taxi cooperatives in the city of Loja in the period April 2020 and March 2021; For which a descriptive, observational, prospective cross-sectional cohort study was used; with a quantitative approach whose purpose was to obtain the incidence of keratoconjunctivitis sicca in the taxi drivers participating in the present research study. The population consisted of 105 taxi drivers from three different taxi cooperatives belonging to the city of Loja. In order to determine this incidence of keratoconjunctivitis, the Schirmer test was used, by means of which it was possible to check the amount of total tear secretion, the McMonnies questionnaire, as well as the Donate questionnaire and to determine which are the risk factors the questionnaire of McMoonies. For the analysis of the data and information collected through the use of the test and the questionnaires, it will be carried out using the Excel program and its representation will be carried out by means of bar graphs. As a result of an investigative study, it was possible to conclude that the incidence of keratoconjunctivitis sicca in taxi drivers is 82.86% belonging to the city of Loja, likewise it was possible to determine which are the main risk factors, with an exposure to environmental smoke or tobacco, considering it the main risk factor